Signatures of Maturity in Cryptocurrency Market (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Since the introduction of Bitcoin in 2009, the cryptocurrency market has experienced exponential expansion. Evolving from sets of transactions primarily conducted on Internet fora into a significant market valued at over 1.2 trillion USD as of August 2023, today cryptocurrency trading occurs 24/7 on more than 600 platforms. Despite its persistent volatility, recurrent speculation bubbles and subsequent market crashes, the trading characteristics of cryptocurrency exchanges are similar to those observed in mature financial markets. Recently, the correlation between the most frequently traded cryptocurrencies, specifically Bitcoin and Etherereum, has increased significantly versus the stock indices and other financial assets, suggesting an emerging connectedness with the global financial markets. This Special Issue collected research studies that make steps towards developing a better understanding of cryptocurrency market, with a particular aim of confirming or denying the growing signs of market maturity. Most submissions focus on price fluctuations in the cryptocurrency exchanges and produce evidence of the cryptocurrency market’s evolution into a valid and interrelated component of the global financial markets. Interestingly, the events related to COVID-19 contributed to the intensification of this process. Some articles address the structure of the cryptocurrency market, including DeFi, the methods of obtaining consensus used, and the environmental impact of these transactions.